THE IMPORTANCE OF SOFT SKILLS TRAINING ON COMPANY PERFORMANCE AT BNI TOLITOLI BRANCH OFFICE - Lahope, Reffaldi R.; Worang, Frederik G.; Gunawan, Emilia (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Soft skills are very important for all company employees to have. Companies are required to improve the soft skills of employees by conducting soft skills training. Soft skills training for employees will provide benefits for the company in supporting the company performance to achieve several objectives. The purpose of this study is to see the importance of soft skills training on company performance, along with exploring the relationship between soft skills training and company performance and to find that soft skills are important for company performance. This research use qualitative methods with using in dept interviews through 20 employees of Bank BNI Tolitoli Branch Office and gather some data from company. The results show that soft skills training are important on company performance. The employees aware about soft skills and thought that soft skills training is important and should be more held by company. The result also show that with using soft skills and develop it, performance of Bank BNI Tolitoli Branch Office is runs well. Online training is very effective in achieving good company performance. Company should accommodate different learning styles so that most employees want to be involved.Â Keywords: analysis importance of soft skills training, soft skills, company performance, banking industry.